Evidence of Jorge: Documentary Traces of a Forced Disappearance in Colombia - Qvortrup, Natalia; Giraldo, Marta (Archivaria, 2022)
Jorge Soto Gallo disappeared on July 15, 1985, during a trip from Medellín to Bogotá in Colombia. Jorge is one of the thousands of disappeared people in Colombia whose families are still searching for answers, yet Jorge’s life and disappearance have been memorialized and recorded through his sister’s work of preserving, cultivating, and activating his personal archive. During recent decades, families of disappeared persons have begun to assemble folders that carry the evidence of disappearances. This article explores the personal archive of Jorge Soto Gallo with the aim of understanding a recordkeeping practice carried out by families and communities, which focuses on disappeared persons and often leads to a broad repertoire of political activism in defence of human rights. We ask, Which records are included, how are they brought together during these periods of upheaval, what do they mean, and what role do they play? We argue that creating and preserving these archives of enforced disappearance act as liberatory memory work (LMW) and as instincts of the families against forces of impunity and oblivion. We show that LMW is a living reality in Colombia that operates on a person-centred level, going beyond transitional justice frameworks, and turning victims into recordkeepers providing the possibility of historical accountability for future generations.